Intra-Arterial Therapies for Metastatic Colorectal Cancer - Wang, David S.; Louie, John D.; Sze, Daniel Y. (Seminars in Interventional Radiology, 2013)
Intra-arterial therapies for unresectable hepatic metastases from colorectal cancer include radioembolization (RE) with yttrium-90 microspheres, transarterial chemoembolization (TACE), hepatic arterial infusion, and percutaneous hepatic perfusion using an organ isolation system. In this article, we discuss our approach toward treatment selection, followed by details of how RE and TACE are performed at our institution.
Keywords: colorectal cancer; liver metastases; radioembolization; drug-eluting beads; irinotecan